2012
DOI: 10.1371/journal.pone.0047295
|View full text |Cite
|
Sign up to set email alerts
|

T2-Signal of Ulnar Nerve Branches at the Wrist in Guyon’s Canal Syndrome

Abstract: ObjectiveTo evaluate T2-signal of high-resolution MRI in distal ulnar nerve branches at the wrist as diagnostic sign of guyon’s-canal-syndrome (GCS).Materials and Methods11 GCS patients confirmed by clinical/electrophysiological findings, and 20 wrists from 11 asymptomatic volunteers were prospectively included to undergo the following protocol: axial T2-weighted-fat-suppressed and T1-weighted-turbo-spin-echo-sequences (3T-MR-scanner, Magnetom/Verio/Siemens). Patients were examined in prone position with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 41 publications
0
21
0
1
Order By: Relevance
“…2). More than that, results of the study demonstrated that it is possible to directly correlate the increased nerve T2w signal as most valuable MR neurographic marker with the DML as the current gold-standard NCS parameter, which underlines that the detected changes in nerve T2w signal express true and functionally relevant nerve lesions [20].…”
Section: Guyon's Canal Syndromementioning
confidence: 77%
See 3 more Smart Citations
“…2). More than that, results of the study demonstrated that it is possible to directly correlate the increased nerve T2w signal as most valuable MR neurographic marker with the DML as the current gold-standard NCS parameter, which underlines that the detected changes in nerve T2w signal express true and functionally relevant nerve lesions [20].…”
Section: Guyon's Canal Syndromementioning
confidence: 77%
“…In Guyon's canal syndrome (GCS), the most distal entrapment neuropathy of the ulnar nerve, patients typically present with motor and sometimes also sensory deficits in the distribution of the distal ulnar nerve branches, the deep motor and the superficial sensory branch. Even at this distal anatomical level at the wrist, where nerve structures are at the limit of current structural resolution, high-resolution MRN has been proven to reliably determine clinically relevant nerve branch injury with high diagnostic accuracy (AUC of 0.94; 95 % CI, 0.85-1.00, specificity 90 %, sensitivity 89.9 %) [20]. In accordance with clinical symptoms, the distal motor branch was predominantly affected.…”
Section: Guyon's Canal Syndromementioning
confidence: 97%
See 2 more Smart Citations
“…As the ulnar nerve passes the intramuscular medial septum and the medial head of the triceps muscle it may be compressed by a locally thickened ligament (sometimes also referred to as the Struther 0 s arcade) (Wehrli and Oberlin 2005). Recent MRI data at 3 T could impressively demonstrate the high sensitivity of MRI in detecting signal changes of the deep motor branch of the ulnar nerve in Guyon's-canal-syndrome (Kollmer et al 2012). Then it is defined by the course of the nerve underneath a retinaculum proximally and further distally underneath the arcuate ligament of Osborne and finally it is covered by the deep aponeurosis of forearm flexor muscles (Assmus et al 2009).…”
Section: Ulnar Nerve Neuropathiesmentioning
confidence: 99%